A Study on Performance of Sago Fine Waste (SFW) as Cement Replacement for Cement Brick - Mohd Zolkfali, Nur Syahirah; A , Suraya Hani; A W, Norhayati (Progress in Engineering Application and Technology, 2023)
One of the new concepts for the production of bricks is the reuse and recycling of construction and demolition waste. Construction and demolition waste refers to the waste generated during the construction, renovation and demolition of buildings. Due to the lack of natural aggregates, it is difficult for manufacturers in emerging regions to find suitable bricks. Recycled construction waste can replace natural resources or other competitive raw materials. The purpose of this research is to determine the sustainable properties of cement brick using Sago Fine Waste (SFW) as a cement replacement to reduce chemical emissions from cement. It also aims to use system reuse, reduce and recycle organic material, and prevent SFW from being improperly treated.The objective of this study is to determine the density, sound absorption test and initial absorption rate (IRA) of sago fine waste (SFW) for cement bricks, as well as to determine the best optimum percentage of sago fine waste (SFW) as cement replacement material for cement bricks. For this study, cement brick samples were prepared with a control, 2%, 4%, 6%, 8%, and 10% SFW with water cement ratios of 0.5 and 0.6. The size of the SFW was less than 0.6 mm. The brick was cast in a mould with a length of 215 mm, a width of 103 mm and a depth of 65 mm, while a size of 28 mm diameter was used for the cylindrical mould. In the first phase of the study, tests on density, sound absorption and initial absorption rate (IRA) were carried out in the Concrete Laboratory and Building Services Laboratory of UTHM Pagoh. The optimum percentage of SFW was determined based on the density test, sound absorption and initial absorption rate (IRA). The results of the density test show that the best lightweight brick and the optimum percentage is SFW10% with a water-cement ratio of 0.5. Besides, for the sound absorption test, the best optimum percentage is SFW10% with water-cement ratio of 0.5, which can absorb sound efficiently, while the best optimum percentage for initial absorption rate (IRA) is SFW2% with water-cement ratio of 0.5, which absorbs less water in one minute. It can be concluded that all sample bricks were satisfactory and met the standard values.